Efficacy of dimethyl disulfide (DMDS) for the control of chrysanthemum Verticillium wilt in Italy. (March 2017) - Pecchia, Susanna; Franceschini, Antonio; Santori, Alberto; Vannacci, Giovanni; Myrta, Arben
Abstract: Chrysanthemum Verticillium wilt caused by V. dahliae is one of the most damaging soil-borne diseases affecting chrysanthemum production in Italy and in Europe. After the definitive phase-out of methyl bromide and the non-inclusion or limitation of other fumigants a great deal of research to identify alternative treatments for controlling soil-borne pathogens has been conducted. One of the possible alternatives is the use of the new fumigant dimethyl disulfide (DMDS), which is also found in minor amounts in nature as a compound that plays a role in the global sulfur cycle. Two greenhouse trials were carried out over two years (2013–2014), to evaluate the efficacy of DMDS (600 kg ha −1 ) on Verticillium wilt development and chrysanthemum stems yield in naturally infected soil. Treatment with DMDS significantly reduced the incidence of Verticillium wilt compared to the untreated control and results were similar to those obtained with a standard chemical fumigation (Chloropicrin or Metam sodium). Furthermore, stem yields obtained with DMDS and standard chemical fumigations were significantly higher than untreated control. This study shows that V. dahliae was not only isolated from diseased tissues, but also from symptomless tissues in residual chrysanthemum stems. Results suggest the importance of removing chrysanthemum residues infected with V. dahliae, for managing Verticillium wilt and the effectiveness of DMDS fumigation as well as standard chemical fumigations in decreasing V. dahliae residual stems colonization. Graphical abstract: Highlights: Efficacy of the new soil fumigant dimethyl disulfide (DMDS) was studied in 2013–2014. Accolade/Paladin ® was assessed to control Verticillium dahliae on chrysanthemum. DMDS decreased significantly Verticillium wilt incidence in the treated plots. DMDS increased significantly the number of marketable chrysanthemum stems. DMDS decreased the presence of V. dahliae in asymptomatic residual stems.